Performance And Agglomeration Study Of Oil Palm Empty Fruit Bunch In A Bubbling Fluidized Bed Gasifier - Amiri, Pooya Lahijani (2011)

(untitled)
Rapid development of modern industry has greatly increased the demand for energy in recent years. Use of lignocellulosic biomass has fulfilled part of this growing demand in developed countries. Biomass gasification is proved to be a promising strategy to convert biomass into biofuel and bioenergy. Oil palm as the main contributor to biomass resources in Malaysia has attracted considerable attention to fulfill the both traditional and renewable energy demands in a sustainable manner. In this project, gasification of oil palm empty fruit bunch (EFB) was investigated in a pilot scale air-blown bubbling fluidized bed.